2014
DOI: 10.11138/ads/2014.5.1.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dentin surface treatments on shear bond strength of glass-ionomer cements

Abstract: SummaryAim. The aim of this in vitro study was to evaluate the effect of different surface treatments on shear bond strength of a conventional glass-ionomer cement (GIC) and a resin-modified glass-ionomer cement (RMGIC) to dentin. Materials and methods. 80 bovine permanent incisors were used. 40 cylindrical specimens of a GIC (Fuji IX GP Extra) and 40 cylindrical specimens of a RMGIC (Fuji II LC) were attached to the dentin. The teeth were then randomly assigned to 8 groups of equal size (n=10), 4 for every ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 55 publications
6
32
1
5
Order By: Relevance
“…A higher shear bond of RMGIC to dentin than GIC (Fuji IX GP Extra) was also reported by Poggio et al 13 when they evaluated the effects of dentin surface treatments on shear bond strength of GICs.…”
Section: Discussionsupporting
confidence: 68%
“…A higher shear bond of RMGIC to dentin than GIC (Fuji IX GP Extra) was also reported by Poggio et al 13 when they evaluated the effects of dentin surface treatments on shear bond strength of GICs.…”
Section: Discussionsupporting
confidence: 68%
“…15 Yeni geliştirilen dental materyallerin dentine bağlanma dayanımları son yıllarda ayrıntılı bir şekilde araştırılmaktadır. 18 Birçok bağlanma dayanımı testi vardır ve in vitro şartlarda en sık kullanılanlarından biri de makaslama bağlanma dayanımı testidir. 19 Bu test yöntemini, kullandığımız materyallerin dentine uygulanan yüzey alanlarının geniş olmasından, kolay ve kabul gören bir yöntem olmasından dolayı tercih ettik.…”
Section: Bulgularunclassified
“…However, the smear debris, which remains in the adhesive interface, becomes an obstacle for ideal bond formation, because it does not have a physiological or morphological connection to the underlying substrate (8)(9)(10). Indeed, it has been demonstrated that smear layer removal with acid etching could improve the bonding performance of GICs to both enamel and dentin substrates (11)(12)(13)(14)(15)(16)(17)(18)(19). When applied to smear layercovered dentin, acid etching not only removes the smear layer by the dissolution of its inorganic part, but it also superficially demineralizes the underlying dentin, which creates microporosities and facilitates mechanical interlocking (14).…”
mentioning
confidence: 99%